Differential Modulation of Photosynthesis, Signaling, and Transcriptional Regulation between Tolerant and Sensitive Tomato Genotypes under Cold Stress - Liu, Hui; Ouyang, Bo; Zhang, Junhong; Wang, Taotao; Li, Hanxia; Zhang, Yuyang; Yu, Chuying; Ye, Zhibiao (PLOS ONE, 2012)
The wild species Solanum habrochaites is more cold tolerant than the cultivated tomato (S. lycopersicum). To explore the mechanisms underlying cold tolerance of S. habrochaites, seedlings of S. habrochaites LA1777 introgression lines (ILs), as well as the two parents, were evaluated under low temperature (4°C). The IL LA3969 and its donor parent LA1777 were found to be more cold tolerant than the recurrent parent S. lycopersicum LA4024. The differences in physiology and global gene expression between cold-tolerant (LA1777 and LA3969) and -sensitive (LA4024) genotypes under cold stress were further investigated. Comparative transcriptome analysis identified 1613, 1456, and 1523 cold-responsive genes in LA1777, LA3969, and LA4024, respectively. Gene ontology (GO) term enrichment analysis revealed that more GO biological process terms were significantly enriched among the up-regulated genes in the two tolerant genotypes, whereas more biological processes were significantly repressed by cold stress in the sensitive one. A total of 92 genes with significant differential expression between tolerant and sensitive genotypes under cold stress were identified. Among these, many stress-related GO terms were significantly enriched, such as ‘response to stimulus’ and ‘response to stress’. Moreover, GO terms ‘response to hormone stimulus’, ‘response to reactive oxygen species (ROS)’, and ‘calcium-mediated signaling’ were also overrepresented. Several transcripts involved in hormone or ROS homeostasis were also differentially expressed. ROS, hormones, and calcium as signaling molecules may play important roles in regulating gene expression in response to cold stress. Moreover, the expression of various transcription factors, post-translational proteins, metabolic enzymes, and photosynthesis-related genes was also specifically modulated. These specific modifications may play pivotal roles in conferring cold tolerance in tomato. These results not only provide new insights into the molecular mechanisms of cold tolerance in tomato, but also provide potential candidate genes for genetic improvement.